The Evolving Role of Blending of the Lid-Cheek Junction in Lower Blepharoplasty. Issue 2 (August 2018) - Rohrich, Rod J.; Mahedia, Monali; Hidalgo, David; Shah, Nilay
Abstract : Background: Lower blepharoplasty has evolved from traditional lower blepharoplasty involving skin-muscle flaps and fat resection to newer concepts that emphasize blending the lid-cheek junction. It is the objective of this review to evaluate these new concepts for their efficacy in blending the lid-cheek junction. Methods: A comprehensive review of literature was performed using PubMed/MEDLINE to identify studies evaluating fat conservation, fat augmentation, fat repositioning, orbicularis retaining ligament (ORL) release, septal reset, and use of fillers in deep cheek fat compartments to obtain aesthetically pleasing lid-cheek junction. Results: A total of 22 studies meeting inclusion criteria and evaluating fat conservation, fat augmentation, fat repositioning, ORL release, septal reset, and use of fillers in deep cheek fat compartments are analyzed and discussed. Conclusions: This review provides the current evidence for various strategies that can be used alone or combined to obtain youthful lid-cheek junction. It provides the current evidence-based scientific rationale for optimal management of the lower eyelid cheek area for facial rejuvenation.